Med-Pharm Games Application as Learning Media for Department of Pharmacy Students - Dessy, Dessy Ratna Sari; Rani Tiara Desty (SEAMEO SEAMOLEC, 2024)
This study aims to produce game-based science learning media, namely Med-Pharm Games for use in learning for Diploma Students Department of Pharmacy. Med-Pharm Games is a knowledge game about the names and uses of drugs, especially in the field of Pharmacy. This game is able to sharpen the brain by finding the appropriate answer based on the statement. This research is a type of development research (research and development). The development model used in this research is ADDIE which consists of (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. This research was conducted to produce the Med-Pharm Games application and the Med-Pharm Games application was validated by media experts and material experts. The data analysis technique used was a questionnaire instrument and descriptive analysis techniques. This games application is easy to use (user friendly) for Android smartphones or laptops or PCs (Windows). Based on media expert validation and material on the feasibility of Android-based learning media, namely Med-Pharm Games with an ideal percentage of 92.67% which is included in the feasible category with a very good predicate.